Computer vision-assisted dietary assessment in youth in urban Ghana: Validity against weighed records and comparison with 24-hour recalls - Gelli, Aulo; Folson, Gloria; Nwabuiku, Odiche; Bannerman, Boateng; Ador, Gabriel; Atadze, Vicentia; Asante, Millicent; McCloskey, Peter; Sow, Doulo; Nguyen, Phuong Hong; Hughes, David (International Food Policy Research Institute, 2023)
Recent estimates suggest that diet related risk factors cause 11 million deaths every year, more than any other factor included in the Global Burden of Disease analyses. These risks have been exacerbated by trends associated with the “nutrition transition,” including increased consumption of unhealthy, processed foods and reductions in physical activity, leading to increases in rates of overweight and obesity. Up-to-date dietary intake data are essential for the development of evidence-based nutrition actions. However, dietary data collection and analysis is complex and expensive. Dietary assessment surveys commonly use the multi pass 24-hour recall (24HR) method that has been validated for use in adults self-reporting their intake and/or that of their young children, and in adolescents. The costs of undertaking a 24HR are of the order of $500 per recall.